Implementation of Qanun Islamic education as local wisdom based on Aliyah´s curriculum - SULAIMAN, SULAIMAN; YUSNAINI, S; SYABUDDIN, SYABUDDIN; JABALIAH, JABALIAH; MASRIZAL, MASRIZAL (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article examines the implementation of Islamic education and teacher’s competence in determing the islamic curriculum, and the limitations regarding islamic education of Madrasah Aliyah in Aceh. The results of presented the implementation of Islamic education of Madrasah Aliyah in Aceh refering to the Aceh qanun Islamic education Number 11 the year 2014. The teachers assigned in Aceh should have good competency and qualified bachelor skills and have the ability to carry out the Islamic education process following the provisions of the Aceh. Overall, the implementation of Islamic education in Aceh is carried out effectively and efficiently.